2000
DOI: 10.1056/nejm200003093421006
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation and Management of Bradycardia

Abstract: There is considerable variation in the resting heart rate among the healthy, asymptomatic population. Spodick and others estimated that the "normal" range of heart rates in the afternoon was 46 to 93 beats per minute for men and 51 to 95 beats per minute for women. 5-7 Nocturnal rates are slower, decreasing during sleep by an average of 24 beats per minute in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
123
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(130 citation statements)
references
References 46 publications
1
123
0
3
Order By: Relevance
“…4 SSS is mainly the result of chronic fibrotic degenerative processes or calcification of the sinus node and/or the surrounding atrial tissues. These processes become more common with increasing age and may occur over years.…”
Section: Aetiologymentioning
confidence: 99%
“…4 SSS is mainly the result of chronic fibrotic degenerative processes or calcification of the sinus node and/or the surrounding atrial tissues. These processes become more common with increasing age and may occur over years.…”
Section: Aetiologymentioning
confidence: 99%
“…4 The SSS is characterized by sinus node dysfunction with an atrial rate inappropriate for physiologic requirements because the sinus node is unable to perform its pacemaking function (Figs 2 and 3). 1,2,5 The combination of CCB and BB is increasingly used in the management of hypertension. Anesthesia can cause myocardial depression in patients on BB 2 and silent myocardial ischemia in those on CCB.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,5 The combination of CCB and BB is increasingly used in the management of hypertension. Anesthesia can cause myocardial depression in patients on BB 2 and silent myocardial ischemia in those on CCB. 6 However, the effect of anesthesia on patients receiving a combination of CCB and BB is unique and was studied by Samad et al, 7 who found that hypotension (systolic BP <90 mm Hg) and bradycardia (HR <50/min) were more common in CCB and BB group (55%) than in BB group (15%) alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acquired AVB with an etiology other than coronary artery disease is normally idiopathic and affects elderly people. Apart from structural heart lesions, additional factors facilitating abnormal automaticity and conduction disorders in the heart among the population of people over 65 years old include: antiarrhythmic agents applied due to arrhythmia and/or heart failure, concomitant renal failure, and electrolyte imbalance [18,19]. The population of elderly people is increasing and so is the number of calls to incidents of collapse, syncope, which might be caused by sick sinus syndrome or AVB.…”
Section: Discussionmentioning
confidence: 99%